Sejarah Perkembangan Tarekat Naqsyabandiyah di Kelurahan Sukajadi, Kabupaten Labuhanbatu Utara - Azhari, Abdi; Siregar, Yusra Dewi; Yasmin, Nabila (Medan Resource Center, 2025)
This article explores the historical transformation of the Naqshbandi Sufi Order in Sukajadi, North Labuhanbatu Regency, with a particular focus on how the order has adapted to the pressures of social modernization and evolving religious contexts. The central research question investigates how the Naqshbandi Order has maintained its relevance and spiritual authority amid changing cultural and societal landscapes. Employing a qualitative research methodology rooted in historical analysis, this study draws on in-depth interviews with community members, a review of relevant literature, and direct observation of religious activities within the order. The findings demonstrate that while the Naqshbandi Order has preserved core mystical teachings and practices, it has also integrated more contemporary forms of community engagement, education, and leadership. These adaptive strategies have enabled the order not only to survive but also to reaffirm its role as a vital spiritual institution in the region. The study concludes that the resilience of the Naqshbandi Order lies in its ability to bridge tradition and modernity, ensuring continuity of Sufi spirituality in a changing world.